SMARESiM: AN IMPROVED MODEL OF E-VOTING SYSTEM BASED ON BIOMETRIC KEY BINDING (International Journal of Engineering and Computer Science, 2013)
E-VOTING is a term used to encompass the various techniques applied, through which the electorate or voters can express their intentions electronically. It entails the use of electronic voting equipment, phones, Personal Data Assistants (PDA), online voting etc. The adoption of e-governance strategy in electioneering processes (using Nigeria context- 36 states) will effectively reduce cost as well as enhancing election activities. What makes an e-voting model acceptable is its ability to properly authenticate voters and provide a secure means through which a voter can express his/her franchise. Adopting biometrics authentication is regarded as an effective method for automatically recognizing, with a high confidence, a person’s identity. This paper therefore, proposes Self-Monitoring Analysis and Reporting E-Voting Simulation Model (SMARESiM), a design model of an evoting system leveraging on Biometric Encryption (BE) viz Biometric key Binding (BKB) which is a secured strategy that entails fusing of biometrics with cryptographic schemes. The main objective of this research is to improve on the already existing E-voting models by fusing and adopting biometric and cryptographic techniques as well as using a secure transmission channel for confidential datasets of a voting process. This work develops a simulation model of an E-voting system which adopts relevant algorithms and mathematical equations with emphasis on biometric security schemes. The simulation of a prototype model of the electronic voting system would be developed using Proteus 7.6 application software (a simulation model). Relevant algorithms and flow models are presented while developing the SMARESiM with PROTEUS ISIS coded in Assembly Language. The prototype model would consist of electronic kiosk polling booths (two e-booths) that are all networked to the state electoral collection center and two state collection centers (in this model) are networked to the national electoral collection center via a VPN backbone. The proposed SMARESiM uses a Virtual Private Network (VPN) as the means of communication between the various polling booths and collection points. The VPN platform provides a fast, safe and reliable means of transmitting data over the internet. The results of validation show that the proposed model facilitates the adoption of E-governance in the developing countries.